Linking Neuroinflammation and Neurodegeneration in Parkinson's Disease. (16th April 2018) - Gelders, Géraldine; Baekelandt, Veerle; Van der Perren, Anke
Abstract : Neurodegenerative diseases such as Parkinson's disease (PD) and Alzheimer's disease (AD) impose a pressing burden on our developed and consequently aging society. Misfolded protein aggregates are a critical aspect of several neurodegenerative diseases. Nevertheless, several questions remain unanswered regarding the role of misfolded protein aggregates and the cause of neuronal cell death. Recently, it has been postulated that neuroinflammatory processes might play a crucial role in the pathogenesis of PD. Numerous postmortem, brain imaging, epidemiological, and animal studies have documented the involvement of the innate and adaptive immunity in neurodegeneration. Whether these inflammatory processes are directly involved in the etiology of PD or represent secondary consequences of nigrostriatal pathway injury is the subject of intensive research. Immune alterations in response to extracellular α -synuclein may play a critical role in modulating Parkinson's disease progression. In this review, we address the current concept of neuroinflammation and its involvement in PD-associated neurodegeneration.